Fluid-structural interaction for turbine blade rib models - Chan, Keith Soon Qi (Nanyang Technological University, 2024)
Aircraft turbine blades experience high stresses and temperatures within engine turbines during flight. Over time, the blade structure undergoes deformation, leading to a phenomenon known as creep. Eventually, the blade structure would fail and crack, necessitating for a replacement. An aircraft would be grounded until the replacement process is completed, resulting in financial losses for airline companies. This paper focuses on rib-turbulated cooling, an internal cooling method for turbine blades. One-way fluid-structure interaction simulations will assess the impact of new rib-turbulated designs. Three-Dimensional (3D) models of rib-turbulated designs will be created through SolidWorks. Using ANSYS Fluent, Computational Fluid Dynamics (CFD) will be conducted using ANSYS Fluent to analyse airflow conditions within an engine turbine and assess the blade's heat transfer performance. The CFD data will be exported to ANSYS Mechanical for Finite Element Method (FEM) analysis to evaluate the structural performance of the new rib protrusion designs. In gas turbine engines, higher turbine inlet temperatures correlate with higher efficiency, making designs that maintain high tip temperatures while sustaining a high fatigue cycle desirable. Various "V Snake" and "W Spline" novel designs were created and tested. The V Snake model exhibited notably higher tip temperatures, with a 10.1% increase over the baseline straight model. The V Snake Centred model showed the highest tip temperature among all models, reaching a maximum tip temperature of 1205.7°C. Although the various W Spline designs displayed high tip temperatures, they were still lower than the V Spline curved designs from previous projects. However, the fatigue cycles of all novel designs were rather low. This project also examined the impact of altering certain geometric parameters of the rib model, specifically the ribs' filleting radius and width. Referring to the baseline straight model, increasing the rib filleting from 0.15mm to 0.25mm resulted in a decrease in tip temperatures, while fatigue cycles increased from 52858 cycles to 56184 cycles. Widening of the ribs led to a slight decrease in tip temperature from 1063.2°C to 1056.8°C and a drop in fatigue cycles from 56184 cycles to 52636 cycles.